Perceived Parental Violence, Sexism, and Attitudes towards Dating Violence against Women - Serap Akgün; Gamze Er Vargün; Özge Ünal (Psikiyatride Güncel Yaklaşımlar, 2022)
The aim of this study was to examine the relationship between perceived parental violence during childhood, sexist attitudes towards women and the attitudes towards dating violence perpetrated by men. For this purpose, data were collected from 351 (201 female, 150 male) university students aged 18-28. A battery of scales including the Attitudes towards Dating Violence Scale, Ambivalent Sexism Scale, and questions about physical and psychological violence from their parents during childhood were administered to the participants. Three hierarchical regression analyzes were conducted to determine the predictors of participants' attitudes towards physical, psychological and sexual dating violence. According to the results of the hierarchical regression analysis, gender predicted positive attitudes towards psychological and sexual dating violence. According to this finding, male university students' attitudes towards psychological and sexual dating violence are more positive than female university students. In the analyzes conducted, the physical violence that the participants experienced from their parents during their childhood positively predicted the positive attitudes towards physical dating violence. When the relationship between sexist attitudes and attitudes towards dating violence is examined, hostile sexism towards women positively predicted positive attitudes towards psychological, physical and sexual dating violence. On the other hand, benevolent sexism towards women positively predicted positive attitudes towards physical dating violence. In conclusion, the findings remark to the role of sexist attitudes towards women and perceived parental violence in childhood on positive attitudes towards dating violence. Determining the variables that predict attitudes towards dating violence seems important for intervention studies aiming to prevent dating violence in romantic relationships.